The method of comparative-historical analysis: a tailor-made approach to public diplomacy research - Hendrik W. Ohnesorge (Place Branding and Public Diplomacy, 2021)
In view of the major methodological challenges which confront researchers in public diplomacy (PD), the paper recognizes the method of comparative-historical analysis (CHA) as an eminently suitable approach for robust empirical studies. The paper starts by exploring different conceptualizations and operationalizations of public diplomacy. Subsequently, four defining characteristics of CHA are identified: (1) CHA starts from a positivist epistemological perspective; (2) CHA-based research usually is concerned with "big questions;" (3) comparative methods are applied in CHA, either across different cases or within cases across time, allowing for in-depth analyses; (4) by considering respective starting points, specific historical developments, and cultural particulars, CHA is committed to methods drawn from historical research, including process tracing and causal narrative. The paper demonstrates that CHA, in view of these characteristics and with its highly interdisciplinary pedigree and methodological eclecticism, is eminently suited for studies exploring PD practices and outcomes. To provide a tailor-made approach for such endeavors, CHA is innovatively combined with the method of structured, focused comparison. Finally, drawing on both the different operationalizations of PD and the requirements of CHA, a comprehensive matrix for CHA-based PD research is presented, offering a tangible framework for future empirical analyses.
Keywords: 330; Public diplomacy; Soft power; Methodology; Comparative-historical analysis (CHA); Structured; focused comparison; Public diplomacy matrix